1 Sacubitril/valsartan in chronic symptomatic heart failure with reduced ejection fraction: first clinical experience from a large uk tertiary centre. (5th June 2017) - Ali, Danish; Riley, Fiona; Kirkland, Stephanie; Hyland, Jacqui; Banerjee, Prithwish
Abstract : Introduction: Sacubitril/valsartan (SV) is a new drug that has recently been approved by the National Institute for Health and Care Excellence (NICE) to be used as an alternative to ACE-inhibitors/Angiotensin Receptor Blockers in patients with symptomatic chronic heart failure with reduced ejection fraction (HFrEF). We report an early clinical experience of SV use in HF patients at a large tertiary cardiac centre in the UK. Methods: Patients with HFrEF (NYHA class II-IV and Left Ventricular Ejection Fraction <35%) seen in the heart failure clinic and started on Sacubtril/valsartan (one tablet 49/51 mg twice daily) from April till October 2016, were retrospectively evaluated. Change in NHYA class, eGFR, up-titration to target dose (one tablet 97/103 mg twice daily), deaths, hospitalizations and patients tolerability to SV were assessed. All patients had either their ACE-inhibitor or angiotensin receptor antagonist stopped at least 48 hours prior to starting sacubtril/valsartan and re-attended the HF clinic at 4 weekly intervals until up-titration was completed. Results: A total of 44 patients were commenced on SV and in 25 patients (57%) up-titration to the target dose was achieved. In 12 patients (27%) an improvement of NYHA class was seen. Nine patients (20%) had symptomatic systolic blood pressure drop of >10 mmHg at follow-up with 3 patients having hyperkalaemia (7%), preventing target dose up-titration. A total of 4 hospital admissions occurred: 2 due to decompensated heart failure (5%), 1 for hyperkalaemia and 1 non-cardiovascular (CV) related. Out of those hospital admissions, 2 patients died (see table). Four patients (9%) had a worsening of the eGFR>10 (without progressive renal failure preventing up-titration) and in 2 patients (5%) the drug was stopped to due intolerability (reported postural dizziness and abdominal pain). Conclusion: The clinical use of SV in our centre has a high rate of tolerability with significant improvement in NYHA class (27%). However, in a large proportion of patients the target dose was not achieved (43%), mainly due to symptomatic hypotension and secondly due to hyperkalaemia (7%). A significant number of patients had a drop in eGFR, but this did not prevent up-titration. Our results confirm that HFrEF patients commencing sacubitril/valsartan require close monitoring of symptoms, renal function and dose titration by a ?specialist heart failure team.